2017
DOI: 10.1089/acu.2017.1251
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Facial Pain with I Ching Balance Acupuncture

Abstract: Background: Trigeminal neuralgia (TN) is the most common cranial neuralgia in adults, with a slightly higher incidence in women than in men. This chronic pain condition affects the trigeminal nerve, also known as the 5th cranial nerve. It is one of the most deeply distributed nerves in the head. Antiseizure drugs are the main biomedical treatment of TN. However, TN is not the only source of facial pain. Background persistent idiopathic facial pain (PIFP) is also a chronic disorder, recurring daily for more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Acupuncture has therapeutic effects on PHN 30,31 and can regulate the dysfunction and impaired activity of the central nervous system induced by PHN detected by functional magnetic resonance imaging (fMRI). These specific effects of acupuncture might result from the cooperation of brain regions engaged in both pain sensation and pain modulation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has therapeutic effects on PHN 30,31 and can regulate the dysfunction and impaired activity of the central nervous system induced by PHN detected by functional magnetic resonance imaging (fMRI). These specific effects of acupuncture might result from the cooperation of brain regions engaged in both pain sensation and pain modulation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have confirmed the therapeutic effects of acupuncture on PHN. These have included case reports and pilot studies which have identified acupuncture as a therapy with promising results for relieving pain without significant adverse reactions 2224. As more and more PHN treatments are developed, acupuncture might have an advantage for analgesia and reducing adverse reactions.…”
Section: Introductionmentioning
confidence: 99%